A study on adverse events following immunisation among COVID-19 vaccine recipients at a tertiary care hospital in Kashmir valley - Shah, Rohul Jabeen; Fazili, Anjum Bashir; Ahmad, Javeed (International Journal Of Community Medicine And Public Health, 2023)
Background: Adverse events following immunization (AEFI) is an event of unexpected medical emergency occurring after vaccination without any causal association with vaccination. It can be any unintended, abnormal laboratory finding or anything. The present study was conducted to evaluate the incidence and severity of AEFI associated with the COVID-19 vaccines. Methods: All the beneficiaries who had received two doses of Covishield and Covaxin vaccine from SKIMS Soura and provided consent were included in this prospective study. Each beneficiary was contacted telephonically. A self- designed questionnaire was used to interview them. The beneficiaries were contacted twice. The data was entered into and analysed using SPSS version 20. Results: A total of 267 participants (52.3%) reported at least one of the AEFI following Covaxin vaccine. It was found that participants with AEFIs following the first dose had more chances to develop them following its second dose and this difference was found to be statistically significant (OR=6.8, p=0.0001). A total of 670 participants (38.0%) reported at least one of the AEFI following Covishield vaccine. The incidence of AEFIs was more after the first dose (31.6%) than that of the second dose (6.4%) and this difference was found to be statistically significant (p<0.0001). Conclusions: Most of the AEFI are minor and can be managed symptomatically. Therefore, these AEFIs should not be a hurdle for vaccination.